Spatial Congruence or Mismatch Between Phylogenetic and Functional Structure of Seed Plants Along a Tropical Elevational Gradient: Different Traits Have Different Patterns - Zhou, Yadong; Wang, Shengwei; Njogu, Antony W.; Ochola, Anne C.; Boru, Biyansa H.; Mwachala, Geoffrey; Hu, Guangwan; Wang, Qingfeng (Frontiers in Ecology and Evolution, 2019)
Compared with species richness, few studies have investigated the patterns and the relationship of phylogenetic and functional structure along elevation gradients. Here, we used general additive models (GAM) to determine the trends of species richness (SR), phylogenetic and functional diversity (PD and FD), phylogenetic structure (NRI), and functional structure (NFRI) of seed plants along the elevation gradient in a tropical mountain of Africa. We measured growth form, fruit type, maximum height, and maximum leaf size of each species, calculated the phylogenetic signal of each trait, and tested the Pearson correlation coefficients between NRI and NFRI of each trait. Our results showed that SR, PD, and FD decrease gradually along the elevation gradient. NRI exhibited a fluctuating pattern along the elevation gradient, while NFRI of the four functional traits showed noticeably different patterns. We concluded that the relationship between phylogenetic and functional structure in different functional traits could be congruent or mismatch along the elevation gradient. Compared with relatively conservative categorical traits (e.g., growth form and fruit type), continuous traits (e.g., height and leaf size) have a random or convergent evolutionary pattern; therefore, they could be more easily affected by the environment and possibly have higher phenotypic plasticity.